Diabetes and diabetes-associated lipid abnormalities have distinct effects on initiation and progression of atherosclerotic lesions - Renard, Catherine B.; Kramer, Farah; Johansson, Fredrik; Lamharzi, Najib; Tannock, Lisa R.; Herrath, Matthias G. von; Chait, Alan; Bornfeldt, Karin E. (The Journal of clinical investigation, 2004)
Diabetes in humans accelerates cardiovascular disease caused by atherosclerosis. The relative contributions of hyperglycemia and dyslipidemia to atherosclerosis in patients with diabetes are not clear, largely because there is a lack of suitable animal models. We therefore have developed a transgenic mouse model that closely mimics atherosclerosis in humans with type 1 diabetes by breeding low-density lipoprotein receptor-deficient mice with transgenic mice in which type 1 diabetes can be induced at will. These mice express a viral protein under control of the insulin promoter and, when infected by the virus, develop an autoimmune attack on the insulin-producing beta cells and subsequently develop type 1 diabetes. When these mice are fed a cholesterol-free diet, diabetes, in the absence of associated lipid abnormalities, causes both accelerated lesion initiation and increased arterial macrophage accumulation. When diabetic mice are fed cholesterol-rich diets, on the other hand, they develop severe hypertriglyceridemia and advanced lesions, characterized by extensive intralesional hemorrhage. This progression to advanced lesions is largely dependent on diabetes-induced dyslipidemia, because hyperlipidemic diabetic and nondiabetic mice with similar plasma cholesterol levels show a similar extent of atherosclerosis. Thus, diabetes and diabetes-associated lipid abnormalities have distinct effects on initiation and progression of atherosclerotic lesions.